\(2x^2-8x=13-3y^2\)
\(\Leftrightarrow2x^2-8x+8=21-3y^2\)
\(\Leftrightarrow2\left(x-4\right)^2=21-3y^2\) (1)
Do \(2\left(x-4\right)^2\ge0;\forall x\Rightarrow21-3y^2\ge0\)
\(\Rightarrow y^2\le7\Rightarrow y^2=\left\{0;1;4\right\}\)
Mặt khác vế trái của (1) là chẵn, 21 là số lẻ \(\Rightarrow3y^2\) lẻ
\(\Rightarrow y^2\) lẻ \(\Rightarrow y^2=1\Rightarrow y=\pm1\)
Thế vào (1) \(\Rightarrow2\left(x-4\right)^2=18\Rightarrow\left(x-4\right)^2=9\)
\(\Rightarrow\left[{}\begin{matrix}x=7\\x=1\end{matrix}\right.\)
Vậy \(\left(x;y\right)=\left(7;1\right);\left(7;-1\right);\left(1;1\right);\left(1;-1\right)\)